The Impact of the Managerial Style on Job Satisfaction Among Secondary Education Teachers in Morocco: Fez-Meknes Academy As A Case Study - Khalid Hamdane; Mohammed El Haissoufi (المجلة الإفريقية للدراسات المتقدمة في العلوم الإنسانية والاجتماعية, 2023)
This study aimed to identify the level of job satisfaction among secondary education teachers affiliated with the Fez-Meknes Academy in northern Morocco, in terms of a number of indicators related to the managerial style adopted in the work environment. We tried to evaluate these indicators by surveying the opinions of a teacher’s sample, which consisted of 373 teachers affiliated with the Fez Meknes Academy, by means of a questionnaire sent to them electronically. The results showed the following: 1- There is an average level of job satisfaction among secondary education teachers affiliated with the Fez-Meknes Academy. 2- The job satisfaction of teachers increases dramatically whenever the relationship is clear between them and the school administration and whenever they feel equality between them and the teachers who are affiliated with the public function status. This satisfaction also increases whenever the school administration intervenes to resolve and settle the differences and behavioral problems of students in the classroom. 3- Job satisfaction increases on average for teachers as the administration pays more attention to their human, social and moral aspects. 4- The level of job satisfaction of teachers affiliated with the Fez Meknes Academy in Morocco is explained through a set of values, namely equality between teachers, their participation in decision-making and the promotion of team spirit. The results were interpreted in the light of previous studies, and the study culminated in the last with some suggestions and recommendations.